Pengembangan Instrumen Asesmen Kemampuan Penalaran Matematis Konten Perbandingan untuk Siswa Fase D - Dini Julia Putri; Armis; Sakur (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2024)
Mathematical reasoning ability is an important skill that students must possess. However, many students have low mathematical reasoning skills. This study aims to develop an assessment instrument for mathematical reasoning ability in comparison content for phase D students that is valid, reliable, and has appropriate discrimination power and difficulty level to train their reasoning. The development model used is a development study with preliminary and formative evaluation stages, including self-evaluation, expert review, one-to-one, small group, and field testing. The results of the rational validity (content, construction, and appearance) of the mathematical reasoning ability questions and questionnaires show scores of 3.8 and 3.7 (out of a maximum scale of 4), with criteria of very valid. Item analysis of the mathematical reasoning ability questions produced 8 valid questions with a reliability value of 0.85, indicating a high level of reliability. From the analysis, there are 3 questions with medium difficulty, 3 easy questions, and 2 difficult questions. The discriminative power of the questions shows 1 question with very good criteria, 5 questions with good criteria, and 2 questions with sufficient criteria. Additionally, from the mathematical reasoning ability questionnaire, 14 valid items and 1 invalid item were obtained; the reliability value of 0.85 indicates high criteria; 12 items have sufficient discriminative power and 2 items have poor discriminative power. Thus, the final product of this study is 8 reasoning questions and 12 items of mathematical reasoning ability questionnaire.